Language Complexity, Narratives and Theory of Mind of Romani Speaking Children - Kyuchukov, Hristo; de Villiers, Jill; Кючуков, Хрісто; де Віллєрз, Джіл (My University, 2019)
The paper presents research findings with 56 Roma children from Macedonia and Serbia between the ages of 3-6 years. The children’s knowledge of Romani as their mother tongue was assessed with a specially designed test. The test measures the children’s comprehension and production of different types of grammatical knowledge such as wh–questions, wh-complements, passive verbs, possessives, tense, aspect, the ability of the children to learn new nouns and new adjectives, and repetition of sentences. In addition, two pictured narratives about Theory of Mind were given to the children. The hypothesis of the authors was that knowledge of the complex grammatical categories by children will help them to understand better the Theory of Mind stories. The results show that Roma children by the age of 5 know most of the grammatical categories in their mother tongue and most of them understand Theory of Mind.У статті представлено результати досліджень, проведених за участі 56 ром-ських дітей з Македонії та Сербії у віці від 3 до 6 років. За допомогою спеціально розробленого тесту було оцінено знання дітьми ромської мови як рідної. Завданням тесту було визначенння рівня розуміння мови у дітей, а також їхнє володіння різними видами граматичних знань, таких як: wh – питання, wh – доповнення, пасивні дієслова, присвійний відмінок, час, граматичний аспект, здатність опановувати нові іменники та прикметники, а також повторення речень. Крім цього, діти отримали два ілюстрованих наративи про «теорію розуму». Гіпотеза авторів полягала в тому, що знання дітьми складних граматичних категорій допоможе їм краще зрозуміти розповіді про «теорію розуму». Результати довели, що ромські діти у віці до 5 років знають більшість граматичних категорій рідної мови, і більшість з них розуміють сутність «теорії розуму».
Мовна складність, наративи й «теорія розуму» ромських дітей
Keywords: Romani; language assessment; language complexity; Theory of Mind; мовна складність; «теорія розуму»